Association of faecal pH with childhood stunting: Results from a cross-sectional study. Issue 1 (13th September 2019) - Hossain, Md. Shabab; Das, Subhasish; Gazi, Md. Amran; Alam, Md. Ashraful; Haque, Nur Muhammad Shahedul; Mahfuz, Mustafa; Ahmed, Tahmeed; Damman, Chris J
Abstract : Background: Gut microbiota plays an important role in the growth of children. The gut of children with optimum growth is enriched in certain species, especially Bifidobacteria and Clostridia. Bifidobacteria and c ommensal Clostridia both contribute to formation of acidic stool, and an elevated faecal pH indicates reduction of these species in the gut. The purpose of the study was to investigate the association of faecal pH with childhood stunting. Methods: In this cross-sectional study, 100 children with length-for-age Z score (LAZ) <−1 aged between 12 and 18 months were enrolled from the ongoing Bangladesh Environmental Enteric Dysfunction study conducted in Dhaka, Bangladesh. LAZ was measured by anthropometry and data on factors affecting linear growth were recorded. Faecal pH measurement was done using pH metre on freshly collected non-diarrhoeal faecal samples following standard procedure. Multiple quantile regression was done to quantify the relation between faecal pH and LAZ scores. Results: The mean LAZ and faecal pH of the children were −2.12±0.80 and 5.84±1.11, respectively. Pearson correlation analysis showed a statistically significant negative correlation between stool pH and the LAZ scores (p<0.01). After inclusion of other factors affecting linear growth into the regression model, a statistically significant inverse association was observed between faecal pH and LAZ score (p<0.01). Conclusion: Elevated faecal pH was found to have a significant association with stunted growth. As an indicator of gut microbiota status, faecal pH might have emerged as a possible indirect determinant of childhood stunting. Trial registration number: NCT02812615